Pengaruh Strategi Komunikasi terhadap Kepuasan Pelanggan: Studi Literatur dalam Konteks Hubungan Bisnis - Nofiyanti; Masduki Asbari; Andira Fajrin (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
Business relationships require proper communication to understand the wishes or satisfaction of customers as business partners who will have an impact on future business development or growth. With the collaboration between business people, it will have a significant positive impact if done correctly and correctly. A big impact will be experienced if groups or business people cannot communicate well and appropriately with customers, this relates to the customer's desire to repurchase products or services that have been offered before. So the researcher in this case is very interested in knowing more clearly the right communication strategy in the business relationship environment between business people and customers because this has a significant impact on the sustainability of a company's business. The method used by researchers is a literature study of several existing journals and articles. The results show that service quality shows a significant positive direction on consumer desire to buy products or services while price and promotion do not have a significant impact on buyer desire. This shows that customer satisfaction greatly impacts the increase in sales and has an effect on increasing the revenue of a company or business entity.